MODEL OF MOBILE TRANSLATOR APPLICATION OF ENGLISH TO BAHASA INDONESIA WITH RULE-BASED AND J2ME - Tedjosurya, Dian Puspita; Suharjito, Suharjito (Bina Nusantara University, 2014)
Along with the development of information technology in recent era, a number of new applications emerge, especially on mobile phones. The use of mobile phones, besides as communication media, is also as media of learning, such as translator application. Translator application can be a tool to learn a language, such as English to Bahasa Indonesia translator application. The purpose of this research is to allow user to be able to translate English to Bahasa Indonesia on mobile phone easily. Translator application on this research was developed using Java programming language (especially J2ME) because of its advantage that can run on various operating systems and its open source that can be easily developed and distributed. In this research, data collection was done through literature study, observation, and browsing similar application. Development of the system used object-oriented analysis and design that can be described by using case diagrams, class diagrams, sequence diagrams, and activity diagrams. The translation process used rule-based method. Result of this research is the application of Java-based translator which can translate English sentence into Indonesian sentence. The application can be accessed using a mobile phone with Internet connection. The application has spelling check feature that is able to check the wrong word and provide alternative word that approaches the word input. Conclusion of this research is the application can translate sentence in daily conversation quite well with the sentence structure corresponds and is close to its original meaning.